Lack of experience is a real danger in the diagnostic process (The Reasoner, 2025)
A  failure to suspect a disease with an atypical presentation and formulate it as a hypothesis is not due to heuristic of representativeness as proposed by Balzaretti but is due to lack of awareness of atypical presentations of a disease due to lack of experience. Thus, lack of experience is a real danger in the diagnostic process.
Keywords: Heuristic; Diagnosis; Experience